Methods matter: Different biodiversity survey methodologies identify contrasting biodiversity patterns in a human modified rainforest — A case study with amphibians. (January 2017) - Whitworth, Andrew; Villacampa, Jaime; Serrano Rojas, Shirley Jennifer; Downie, Roger; MacLeod, Ross
Highlights: Biodiversity recovery following habitat change is often difficult to determine. We assess whether different surveys at the same site indicate different responses. Survey methodologies identified contrasting patterns in a human modified rainforest. This was true for species richness, diversity, abundance and community structure. Arboreal amphibians might be more sensitive indicators than terrestrial communities. Abstract: Understanding how well tropical forest biodiversity can recover following habitat change is often difficult due to conflicting assessments arising from different studies. One often overlooked potentially confounding factor that may influence assessments of biodiversity response to habitat change, is the possibility that different survey methodologies, targeting the same indicator taxon, may identify different patterns and so lead to different conclusions. Here we investigated whether two different but commonly used survey methodologies used to assess amphibian communities, pitfall trapping and nocturnal transects, indicate the same or different responses of amphibian biodiversity to historic human induced habitat change. We did so in a regenerating rainforest study site located in one of the world's most biodiverse and important conservation areas: the Manu Biosphere Reserve. We show that the two survey methodologies tested identified contrasting biodiversity patterns in a human modified rainforest. Nocturnal transect surveys indicated biodiversity differences between forest with different human disturbance histories, whereas pitfall trap surveys suggested no differences between forest disturbance types, except for community composition. This pattern was true for species richness, diversity, overall abundance and community evenness and structure. For some fine scale metrics, such as species specific responses and abundances of family groups, both methods detected differences between disturbance types. However, the direction of differences was inconsistent between methods. We highlight that for assessments of rainforest recovery following disturbance, survey methods do matter and that different biodiversity survey methods can identify contrasting patterns in response to different types of historic disturbance. Our results contribute to a growing body of evidence that arboreal species might be more sensitive indicators than terrestrial communities.